Creative Collaborative Virtual Environments - Eustáquio, Luís (2022)
The authors propose to define Creative Collaborative Virtual Environments (CCVEs), as platforms for collaborative and distributed creation in online communities. This will be established by examining virtual worlds as agents of change towards new creative and collaborative models. CCVEs are grounded on three key elements: creation, collaboration, and distribution. These relate not only to the technical, but also to the social layers of virtual online communities. Shared creativity and distributed authorship are approached as examples of specific dynamics rooted upon these three elements. The concept of CCVE is important to the design of emerging virtual worlds, specifically regarding the preservation of affordances for collaborative creativity. Discussion based on these observations demonstrates how collaborative creation of new content and meaning takes place in CCVEs, and how they transform communicative and creative agency in digital communities.